WHISTLEBLOWING SEBAGAI PEMODERASI HUBUNGAN SKEPTISISME PROFESSIONAL DAN BEBAN KERJA TERHADAP PENDETEKSIAN FRAUD - Ni Nyoman Arista Widiasuari; I Wayan Gde Yogiswara Dharma Putra; Putu Gede Wisnu Permana Kawisana (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2025)
This study aims to empirically test the influence of professional skepticism and workload on fraud detection with whistleblowing as a moderator at the Bali Provincial BPKP Representative. There is an inconsistency in the results of previous researchers and a lack of studies that examine fraud detection and whistleblowing. Researchers see an opportunity to re-examine the factors that affect fraud detection. Using the purpose sampling method , as many as 59 auditors used the SEM method based on partial least square and processed using the SmartPLS version 4.0 program. The results of this study found that the skepticism of professional auditors had a positive effect on fraud detection, while the workload had a negative effect on fraud detection. In addition, whistleblowing interactions do not moderate the influence of professional skepticism on fraud detection, and whistleblowing interactions strengthen the influence of workload on fraud detection. Keywords: Professional Skepticism, Workload, Whistleblowing, and Fraud Detection